PLASMAPHERESIS VERSUS INTRAVENOUS IMMUNOGLOBULINS IN GUILLAIN BARRE SYNDROME, THE THERAPEUTIC OUTCOMES: Guillain Barre Syndrome, the Therapeutic Outcomes - Asghar, Syed Parvez; Mubarik, Humera; Shams, Nadia; Cheema, Muhammad Babar; Shah, Shahnaz (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the therapeutic outcomes of plasmapheresis with intravenous immunoglobulins (IVIG) for Guillain Barre syndrome.Study Design: Randomized controlled trial.Place and Duration of Study: Medicine department; PNS Shifa Hospital Karachi from Jan 2011 to Jun 2012.Patients and Methods: Adult patients admitted to internal medicine department with the diagnosis of Guillain Barre Syndrome (GBS) fulfilling the inclusion and exclusion criteria were included after taking ethical approval and informed consent. They were randomly assigned to plasmapheresis and IVIG treatment groups. Their presenting features, investigations and management plan were followed over 6 months duration. Hughes disability scale for Guillain Barre syndrome was documented and compared at admission, 4 weeks, 12 weeks and 6 months by non-parametric tests via SPSS version 17.Results: Total 36 patients (31 males & 5 females) were included. Mean age was 37 ± 15 (18-70) years, mean duration of symptoms 11.6 ± 12.7 days. Plasmapheresis and IVIG groups were comparable with respect to age and gender (p>0.05). Significant improvement of mean disability score was observed in each group from baseline score (p0.05). Variants of GBS observed were AIDP (50%), AMAN (31%) and AMSAN (19%).Conclusion: Our study suggests that both plasmapheresis and intravenous immunoglobulins are useful and effective modes of treatment for Guillain Barre Syndrome. Significant short term improvement was observed in the IVIG group at 4 weeks of treatment; however no significant difference in therapeutic outcome observed between the two groups on further follow up of 6 months. Thus focusing the need of further large scale regional studies to analyze various factors contributing to this short term but significant improvement with IVIG treatment observed in this study.